2021
DOI: 10.1155/2021/3101146
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Ameliorates Microglia Activation by Targeting MicroRNA-221/222-IRF2 Axis

Abstract: Background. Propofol is a widely used intravenous anesthetic drug with potential neuroprotective effect in diverse diseases of neuronal injuries such as traumatic brain injury and ischemic stroke. However, the underlying molecular mechanism remains largely unknown. Methods. Real-time qPCR, enzyme-linked immunosorbent assay, and Western blotting were used to identify the expression pattern of miR-221/222, inflammatory genes, cytokines, and IRF2. The biological roles and mechanisms of propofol in microglia activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…3c), none of which have been implicated in regional microglial signatures. Genes involved in microglia polarization (e.g., Irf8 62 and Stat3 63 ), activation and inflammatory response (e.g., Spi1 64 and Irf2 65 ), and establishment of microglia identity and immune response (e.g. Sall1 66 , Sall3 67 , Etv5 68 , and Zeb1 69 all have high mean average (A) values in both cortex and hippocampus microglia topics.…”
Section: Resultsmentioning
confidence: 99%
“…3c), none of which have been implicated in regional microglial signatures. Genes involved in microglia polarization (e.g., Irf8 62 and Stat3 63 ), activation and inflammatory response (e.g., Spi1 64 and Irf2 65 ), and establishment of microglia identity and immune response (e.g. Sall1 66 , Sall3 67 , Etv5 68 , and Zeb1 69 all have high mean average (A) values in both cortex and hippocampus microglia topics.…”
Section: Resultsmentioning
confidence: 99%
“…A number of mechanisms have been proposed to account for propofol anti-inflammatory effect in microglia, including downregulation of TLR4 expression ( Qin et al, 2013 ), inactivation of GSK-3β ( Gui et al, 2012 ), inhibition of NMDA receptor and NADPH oxidases ( Luo et al, 2013 ) as well as suppression of miR-155 and miR-221/222 ( Zheng et al, 2017 ; Xiao et al, 2021 ). Recent study reported that propofol regulated the activity of HIF-1α to reduce prostate cancer cells malignancy ( Huang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the anti-inflammatory transcription factor Irf2 has been identified as a direct target gene of miR-221/222, binding its 3'-untranslated region to inhibit its translation [ 74 ]. Propofol can inhibit microglial activation through the miR-221/222-Irf2 axis [ 75 ]. MiR-221 and miR-222 are involved in regulating physiological vascular processes in healthy organisms, yet they also promote a malignant phenotype by mediating the proliferation, differentiation, and invasive capacity of cancer cells [ 76 ].…”
Section: Mechanisms Underlying Gaa-microglia Interactionsmentioning
confidence: 99%